State practices in the processes of “patrimonialization” of memory sites in the City of Buenos Aires (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
The aim of this article is to address the notion of statehood by studying the transformation of former Clandestine Centers of Detention, Torture and Extermination in cultural heritage in Buenos Aires. I introduce some considerations to examine the role of the State in the implementation of memory policies, by paying special attention to how heritage experts like archaeologists and conservationists intervene on the materialities of these Sites of memory. I analyze how those memory policies are produced and implemented; what kind of actors participate in those processes (workers, state officials, human rights organizations, relatives of victims, survivors form the Clandestine Centers of Detention, Torture and Extermination, professionals, experts, among others); what different logics are expressed in them; how these State practices are legitimated and which notions of “truth” emerge
Keywords: Heritage; Sites of memory; State; Experts.